ANALISIS KEJADIAN STUNTING PADA BALITA DI DESA PASIRDOTON KECAMATAN CIDAHU KABUPATEN SUKABUMI PROVINSI JAWA BARAT TAHUN 2017-2018 - Putri Azzahroh; Linda Agustina (Jurnal Ilmu dan Budaya, 2020)
Background : Stunting is the main problem that has an ampact on socioeconomic life in society. The prevalence of short toddler in Indonesia is still high at 29% and is a health problem that must be addressed. In West Java, the problem of malnutrition, especially stunting prevalence is still very high 32.9% . In Sukabumi Regency there are 10 village; the incidance rate of stunting toddlers is 16.7% 88 of 528 toddlers. Nutritional deficiency at early age increases infant and child mortality, it makes the sufferer easy to get sick and get no maximum body posture as well as reduced cognitive abilities in patients. Objective: The research aims to determine the analysis of the incidence of stunting in infants at pasirdoton Village, Cidahu District, Sukabumi Regency, West Java province, 2018. Methodology : This is analytic observations research with case control design, with a popolation of 176 respondents. Data was analyzed with chi square formula. Result : The result show that out of 176 respondents with 88 stunting infants and 88 nonstunting infants, there is a significant relatioship between breastfeeding  history (ρ = 000), birth weight (ρ = 000), and maternal nutritional status during pregnancy (ρ = 001) with the incidence of stunting. Conclusions and suggestions :  History of breastfeeding, low birth weight and maternal nutritional status during pregnancy have a severe impact on the incidance of stunting in pasirdoton Village, Cidahu, District, Sukabumi. Optimization of the provision of counseling routinely accompanied by the provision of flyers related to the incidance of stunting is necessary.